Perbedaan Persen Lemak Tubuh, Konsumsi Lemak, Karbohidrat Dan Air Pada Remaja Putri Yang Overweight Dan Non Overweight Di Fakultas Ilmu Kesehatan UMS - Rahmawati, Dini Desia; , Ir. Listyani Hidayati, M.Kes; , Pramudya Kurnia, STP, M.Agr (2014)
Background: The prevalence of overweight worldwide has increased in the last 30 years. One of the age group that is at risk of overweight are adolescent group.Overweight in adolescents need attention, because overweight that appear in adolescence tend to continue into adulthood and elderly. Purpose : To know difference between percent body fat, fat intake, carbohydrate and water consumption in adolescent women with overweight status and non overweight status in the faculty of health at Muhammadiyah University Of Surakarta Method of the Research : The research implemented a survey-observational with cross-sectional approach. Subject of the research is young womenwith overweight status and non overweight status. Subject selected by using simple random sampling. Data of fat, carbohydrate and water intakewas taken by using recall form 3x24 hours.Data ofpercent body fat was taken by usingskinfold caliper. Data was analyzed by using Mann-Whitney dan independent t-test. Result : adolescent women who are overweight 76.5% had a body fat percent fat, 47.1% had a moderate deficit of fat consumption, 44.1% had a moderate deficit carbohydrate consumption and 73.5% had less water consumption.Normal nutritional status group 64.7% had a body fat percent at a low level, 50% had a severe deficit of fat consumption, 44.1% had a severe deficit of carbohydrate consumption and 58.8% had less water consumption. Conclusion : There had been differences in percent body fat, fat and carbohydrateintakebetween adolescent women with overweight status and non overweight status. There hadnot beendifferences in water intake between adolescent women with overweight status and non overweight status.